Synthesis of low-loss yttrium iron garnet (Y₃Fe₅O₁₂) via the microemulsion technique and its synthesis variation effects on its properties - Manap, Masni (2013)
Yttrium iron garnet, Y₃Fe₅O₁₂ (YIG), is a material widely used in electronic devices for the microwave region from 300 MHz to 100 GHz range. Even though the technology involving ferrites is advancing, there is still a lack of understanding and systematic examinations on how losses in ferrites occur and how to control them especially at UHF or higher frequencies. In this work, YIG powders were prepared via the microemulsion technique and different approaches of bulk preparation were employed to attempt production of extremely low loss YIG. The loss of conventional-uniaxial sample, monodisperse-uniaxial sample and monodisperse-CIP sample was studied for samples sintered at relatively low temperature and up to fairly high temperature. YIG was produced by the microemulsion technique as the growth of the precursor was controlled by a water-in-oil emulsion. The aqueous solution consists of (Y(N03h·6 H20) and (Fc(N03) ·9 H-O). Cetyltrirnethyammonium Bromide (CTAL3) was used as the surfactant and n-octane as the oil phase. Ammonium hydroxide solution which acts as a reducing agent was added to the aqueous solution to form precipitates. Then, the precipitates were separated by centri fugation, washed with ethanol and then dried at 80 OC for 12 h. The dried precipitate was calcined at 600 QC for 2 h and ground into powder form. Three torroidal samples were prepared which is conventional-uniaxial sample, monodispersion-uniaxial sample, and monodisperse-CIP sample were sintered at different temperatures. The particle size was confirmed by Transmission Electron Microscopy (TEM), the thermal analysis was performed using a Thermal Thermogravimetric Analyzer (TGA), the phase was characterized uSll1g X-ray diffraction (XRD) and morphology was observed by Field Emission scanning electron microscopy (FeSEM). The permeability and rf energy loss of the samples was studied using an impedance material analyzer. The TEM results show that the particles are in the nanometer range with an average of 24 nm. The crystallization temperature of the sample can be deduced to be at I 145°C as observed from the TGA curve. The XRD results show that the full phase of YlG is formed at l200°C. FeSEM micrographs and grain size distributions for the samples with different preparation techniques show the evolution of microstructure as the grain size increases with the increase of the sintering temperature. The micrographs clearly illustrate the evolution of the particle constituent to the formation of necks which lead to grains development over the sintering temperature range. The conventionally prepared and rnonodispersc sample show the correlation between magnetic loss, phase purity and grain size as it decrease with the decrease of grain size and phase purity. The monodisperse-CIP sample shows a different trend where it has a big grain size but low loss. We speculate that the monodisperse-CIP samples have significant numbers of pores that can act as pinning centers to the domain wall movements thus decreasing the magnetic loss of the sample. All the samples exhibit lower loss with tan () lower than 10.1 comparable to previous research results.